Pigmented villonodular synovitis of the thoracic spine: case report and review of the literature - Arnold,Paul M. (2009)
Pigmented Villonodular Synovitis (PVNS), a lesion of the synovial tissues, is rarely found in the spine. We present a 73-year-old male with increasing lower extremity weakness and paresthesias. MRI scans revealed disc herniation and spinal cord compression at the T11-T12 and T12- L1 levels. Intraoperative exploration revealed an epidural mass originating in the T12 lamina, compressing the spinal cord at T11-T12. Pathologic examination was consistent with pigmented villonodular synovitis.